Repercussões da violência de gênero: um estudo com base nas histórias de mulheres que buscaram ajuda - Menzani, Rosana Maria (Universidade Federal de São Carlos, 2022)
Several studies show that the many different situations of violence are considered a serious public health issue. Among the violence types that exist, the one against women, understood as gender-based violence, is considered a universal problem, regardless of the country's culture, level of education, religion, socioeconomic status or level of development. In this sense, this study focused on gender violence, based on the narratives of the women interviewed, seeking to understand the stories and experiences of women in situations of violence, and paying special attention to the role of the care network that assists women in situations of violence. This is a qualitative and exploratory study, carried out through interviews with women who have experienced domestic violence, all of whom are treated at a Specialized Reference Center for Social Assistance (CREAS) in a city in the countryside of the state of São Paulo (SP). The results show that women suffered all types of violence, ranging from humiliation to deprivation of freedom and food, verbal, psychological and physical aggression, among others; not counting on family and community support to deal with the situation and showing insecurity to trust the professionals and services of the care network that answers to women in situations of violence. In conclusion, it is necessary to discuss and think collectively about more effective actions and strategies to provide attention, prevention and recovery of gender violence victims, based on a network that, in fact, is supportive and assists women throughout their journey seeking help.
Repercussions of gender-based violence: a study based on the stories of the women who sought help
Keywords: Violência contra a mulher; Violência de gênero; Violência e saúde; Violência e saúde da mulher; Violence against women; Gender violence; Violence and health; Violence and women's health; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA